This preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: The Laplace Transform Definition: Let f ( t ) be a function defined on the half–line [0 , ∞ ) , the Signal < Function > assume that f is piecewise continuous and does not grow faster than all polynomials at ∞ . The Laplace Transform of f is de fined as L{ f ( t ) } ( s ) def = R ∞ e st f ( t ) dt def = lim A →∞ R A e st f ( t ) dt , for s > . We often write F ( s ) for L{ f ( t ) } ( s ) and G ( s ) for L{ g ( t ) } ( s ) , etc. Consider F ( s ) an encoding of f ( t ) . Some Facts 1) The Laplace transform is linear: L{ c 1 f 1 + c 2 f 2 } = c 1 L{ f 1 } + c 2 L{ f 2 } . 2) The Laplace transform is one–to–one: L{ f } = L{ g } = ⇒ f = g . Examples: a) f ( t ) = t = 1 . L{ t } ( s ) = lim A →∞ R A e st t dt = lim A →∞ 1 s e st t = A t =0 = 1 s lim e sA  {z } → e s  {z } =1 ! = 1 s : L{ 1 } ( s ) = 1 s . 2 b) f ( t ) = t n for n > . R t n e st dt = 1 s t n e st + n s R t n 1 e st dt = ⇒ R A t n e st dt = 1 s t n e st A + n s R A t n 1 e st dt = ⇒ R ∞ t n e st dt = n s R ∞ t n 1 e st dt = ⇒ L{ t n } ( s ) = n s · L{ t n 1 } ( s ) . c) Applying this with n = 1 , 2 , 3 ,... gives L{ t } ( s ) = 1 s , L{ t 1 } ( s ) = 1 s 1 s = 1 s 2 , L{ t 2 } ( s ) = 2 s 1 s 2 = 2 s 3 , L{ t 3 } ( s ) = 3 s 2 s 3 = 3!...
View
Full
Document
This note was uploaded on 09/07/2010 for the course PHY 303L taught by Professor Turner during the Spring '08 term at University of Texas.
 Spring '08
 Turner

Click to edit the document details